Poverty Treatment Effectiveness in the Era of Pandemic COVID-19 With the Role of the Baitul Maal Wat Tamwil - Vabila Ananta Setya; Tika Widiastuti (AFEBI Islamic Finance and Economic Review, 2021)
Islam teaches to minimize the gap between the rich and the poor through the teachings of Zakat, Infaq and Sedakah (ZIS). Indonesia is one that is included in the red zone of a poor country with various potentials and problems. The problem that will be examined in this research in general is how to strengthen economic institutions run by BMT in poverty reduction efforts. The purpose of this study is to reveal that BMT financing is effective in reducing poverty, where most respondents can increase their income after receiving BMT financing as an effort to reduce poverty and find out what efforts / policies have been established by the government to overcome poverty during the COVID-19 pandemic.